Treatment of acute myeloid leukemia or myelodysplastic syndrome relapse after allogeneic stem cell transplantation with azacitidine and donor lymphocyte infusions: a retrospective multicenter analysis from the German cooperative transplant study group - Schroeder, Thomas; Klein, Stefan; Luft, Thomas (Biology of blood and marrow transplantation, 2015)
To expand the current knowledge about azacitidine (Aza) and donor lymphocyte infusions (DLI) as salvage therapy for relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and to identify predictors for response and survival, we retrospectively analyzed data of 154 patients with acute myeloid leukemia (AML, n = 124), myelodysplastic (MDS, n = 28), or myeloproliferative syndrome (n = 2). All patients received a median number of 4 courses of Aza (range, 4 to 14) and DLI were administered to 105 patients (68%; median number of DLI, 2; range, 1 to 7). Complete and partial remission rates were 27% and 6%, respectively, resulting in an overall response rate of 33%. Multivariate analysis identified molecular-only relapse (hazard ratio [HR], 9.4; 95% confidence interval [CI], 2.0 to 43.5; P = .004) and diagnosis of MDS (HR, 4.1; 95% CI, 1.4 to 12.2; P = .011) as predictors for complete remission. Overall survival (OS) at 2 years was 29% ± 4%. Molecular-only relapse (HR, .14; 95% CI, .03 to .59; P = .007), diagnosis of MDS (HR, .33; 95% CI, .16 to .67; P = .002), and bone marrow blasts <13% (HR, .54; 95% CI, .32 to .91; P = .021) were associated with better OS. Accordingly, 2-year OS rate was higher in MDS patients (66% ± 10%, P = .001) and correlated with disease burden in patients with AML. In summary, Aza and DLI is an effective and well-tolerated treatment option for patients with relapse after allo-HSCT, in particular those with MDS or AML and low disease burden. The latter finding emphasizes the importance of stringent disease monitoring and early intervention.